2022
DOI: 10.1186/s13034-022-00482-x
|View full text |Cite
|
Sign up to set email alerts
|

Increase in admission rates and symptom severity of childhood and adolescent anorexia nervosa in Europe during the COVID-19 pandemic: data from specialized eating disorder units in different European countries

Abstract: Background The COVID-19 pandemic, associated with confinement and social isolation, seems to have impacted the course of many mental disorders in children and adolescents. An increase in hospital admission rates for juvenile anorexia nervosa (AN) has been documented in many regions of the world. However, data from Europe are scarce. Methods We asked clinicians in specialized eating disorder units in hospitals of maximum care in France, Germany, Ita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 25 publications
2
32
1
4
Order By: Relevance
“…According to previous studies [ 7 ], young patients with AN reported that they had lost their daily life structure, especially during school closures [ 32 ]; according to Zeiler et al [ 7 ], they complained of participating in fewer outdoor activities, including sports, during the lockdowns, which then triggered weight phobia. In addition, they had more spare time and experienced more boredom, which led to increased activity in social media, especially on websites glorifying slimness and a well-trained body [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies [ 7 ], young patients with AN reported that they had lost their daily life structure, especially during school closures [ 32 ]; according to Zeiler et al [ 7 ], they complained of participating in fewer outdoor activities, including sports, during the lockdowns, which then triggered weight phobia. In addition, they had more spare time and experienced more boredom, which led to increased activity in social media, especially on websites glorifying slimness and a well-trained body [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies point to a lockdown-induced weight gain in children and adolescents [ 35 ]. In a previous investigation, we reported that patients had assumed to have put on weight during the first lockdown and felt bullied because of “fatness” after their return to school, thus leading to increased efforts to lose weight [ 32 ]. Accordingly, it is well known that intended weight loss may lead to reduced eating and exaggerated participation in sports with the consequence of starvation.…”
Section: Discussionmentioning
confidence: 99%
“…A study has reported a sharp rise in hospital admissions for eating-excretion disorders across Europe during the CQVID-19 pandemic. 29 Another study reported elevated levels of abnormal disorders-related behaviors in patients with eating disorders, showing marked worsening of symptoms. [30][31][32] However, there was also evidence that some people with eating disorders didn't show signi cant worsening of symptoms due to lack of work and social stress during isolation.…”
Section: Covid-19 Pandemic and Eating-excretion Disordersmentioning
confidence: 99%
“…Prior research has demonstrated that family support is important to aid ED treatment outcomes and greater likelihood of patient recovery [ 12 , 13 ]. Additionally, the alleviation of stress on the family unit has been shown to be an important factor in the success of ED-related treatment and recovery [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has demonstrated that family support is important to aid ED treatment outcomes and greater likelihood of patient recovery [ 12 , 13 ]. Additionally, the alleviation of stress on the family unit has been shown to be an important factor in the success of ED-related treatment and recovery [ 12 ]. Nonetheless, the COVID-19 pandemic has led to increased economic burden and thus stress on families due to factors such as a decrease in working hours, loss of job, or loss of insurance.…”
Section: Introductionmentioning
confidence: 99%